Perbedaan Kematangan Sosial Siswa yang Berasal dari Sekolah Homogen dan Sekolah Heterogen - Ramanda, Peni; Khairat, Imalatul (Jurnal Kajian Bimbingan dan Konseling, 2017)
The purposes of this study is to describes: (1) the social maturity of students from homogeneous school and heterogeneous schools; (2) to examine whether there is a difference of social maturity levels of students from the homogeneous schools and heterogeneous schools. The samples of this quantitative research are 206 students from Madrasah Aliyah Swasta Ar-Risalah and Madrasah Aliyah Swasta Tarbiyah Islamiyah Batang Kabung. Sample were chosen using proportional random sampling techniques. The instrument used in this research is the scale of the social maturity of students. The data were analyzed with descriptive statistics and t-test. The research findings shows that: (1) the social maturity of students from homogeneous school heterogeneous schools were on a high category; (2) there is a difference of social maturity levels of students from a homogeneous schools and heterogeneous schools, where the level of social maturity of students from heterogeneous schools is higher.